A nondestructive testing method for magnetic properties of metal components
Through the magnetic performance of the high -end equipment metal component, the data of the stagnation line and the basic magnetization curve is used to obtain data, and the state of damage is judged to solve the problem that it is difficult to quickly and accurately detect the internal defects of metal components in existing technology. Fast loss of loss.
Patent Information
- Application Number
- CN202410603779.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-15
AI Technical Summary
The prior art is difficult to quickly and accurately perform non-destructive testing of internal defect changes on metal components in high-end equipment, and traditional methods are time-consuming and require high requirements for inspectors, so they cannot meet the needs of accurate and fast non-destructive testing.
Using non-destructive testing methods for the magnetic properties of metal components, the hysteresis loop or basic magnetization curve of the metal components is tested to obtain data such as coercivity and magnetic permeability, and the damage status of the components is judged by the changes in these data.
The rapid, effective non -destructive detection of high -end equipment metal components can be achieved, it can judge its internal stress changes, simplify the detection process, improve the detection efficiency, and guide the establishment and non -destructive evaluation of the material damage model.
Smart Images

Figure CN118519082B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nondestructive testing, and in particular to a method for nondestructive testing the magnetic properties of a metal component. Background Art
[0002] For various types of industrial equipment metal components, changes in their internal defect states will affect the performance of the components under various service conditions. Monitoring the defect states of key metal components can ensure the reliability of the components in extreme environments, thereby ensuring the safety and overall performance of mechanical equipment. Therefore, in high-end equipment industries such as aerospace, the detection of defect state changes in metal components has extremely important engineering significance. However, most of the current metal defect state detection is mainly sampling detection, which is a destructive detection and difficult to quantify. Therefore, there is an urgent need to develop an advanced method of fast and accurate non-destructive testing, which will not only help improve detection efficiency, but also better maintain equipment, ensure product quality, and play a key role in engineering and manufacturing.
[0003] At present, the main methods used to detect micro-defect structural changes in metal components of high-end equipment such as aircraft engine bearings and blades mainly rely on X-ray diffractometers, scanning electron microscopes, transmission electron microscopes and other equipment. These methods provide high surface or spatial resolution by observing metal samples, and can observe the shape and distribution of defects in detail. However, these methods have obvious limitations: first, they have high requirements for the surface quality of the samples, and second, the operation is time-consuming and has high requirements for the inspectors. Most importantly, they cannot meet the needs of accurate and rapid non-destructive testing of components. Summary of the invention
[0004] In view of this, in order to solve the current problem of being unable to quickly and accurately detect changes in internal defects of high-end equipment metal components, the present invention provides a method for non-destructive testing of the magnetic properties of metal components. On the one hand, the equipment is used to test the hysteresis loop or basic magnetization curve of the metal component to obtain data such as coercive force and magnetic permeability; on the other hand, the change in its damage state is judged by the degree of change in coercive force and magnetic permeability, thereby realizing non-destructive testing of the magnetic properties of metal components of high-end equipment.
[0005] The technical purpose of the present invention is achieved in this way:
[0006] The present invention provides a method for nondestructive testing of magnetic properties of metal components, comprising the following steps:
[0007] S1: Clean impurities on the surface of metal components;
[0008] S2: Predict the magnetic properties of the metal component n times according to the shape of the metal component, and obtain the magnetic property test error based on the average magnetic property data of the metal component predicted n times;
[0009] S3: Perform n formal measurements on the magnetic properties of the metal component, calculate a damage evaluation index based on the average magnetic property data of the metal component obtained from the n formal measurements, and determine the damage state of the metal component based on the damage evaluation index and the magnetic property test error.
[0010] On the basis of the above technical solution, preferably, the shape of the metal component is an open-circuit component or a closed-circuit component.
[0011] On the basis of the above technical solution, preferably, the magnetic properties of the metal component include coercive force and initial magnetic permeability, and the magnetic property test error includes a coercive force test error Δ1 and an initial magnetic permeability test error Δ2.
[0012] On the basis of the above technical solution, preferably, when the shape of the metal component is an open circuit component, the magnetic property measured is coercive force, the average magnetic property data is average coercive force data, the magnetic property test error is Δo, and Δo=Δ1;
[0013] When the shape of the metal component is a closed-circuit component, its measured magnetic properties are coercive force and initial magnetic permeability, the average magnetic property data are average coercive force data and average initial magnetic permeability data, and its magnetic property test error is Δc, and Δc=Δ1+Δ2.
[0014] On the basis of the above technical solution, preferably, the calculation formula of the coercivity test error Δ1 is:
[0015]
[0016] Where Hc represents the coercivity data, Hc max and Hc min Hc is the maximum and minimum coercivity data obtained in n times of prediction. e is the average coercivity data obtained in n times of prediction;
[0017] The calculation formula for the initial permeability test error Δ2 is:
[0018]
[0019] In the formula, μ i represents the starting magnetic permeability data, and are the maximum and minimum initial permeability data obtained in n times of prediction, is the average initial magnetic permeability data obtained in n pre-measurements.
[0020] Based on the above technical solution, preferably, the damage evaluation index of the open circuit component is for:
[0021]
[0022] In the formula, is the related constant of the open circuit component, and its value is 0.85-1.25; is the average coercive force change rate data obtained from n formal measurements of the open circuit component;
[0023] Damage evaluation index of closed circuit components for:
[0024]
[0025] In the formula, is the related constant of the closed circuit component, and its value is 0.85-1.25; is the structural coefficient of the closed-circuit component, and its value is 1-1.05; is the average coercive force change rate data of the closed-circuit component obtained in n formal measurements; It is the average initial permeability change rate data of the closed-circuit component obtained in n formal measurements.
[0026] On the basis of the above technical solution, preferably, the process of judging the damage state of the open circuit component is:
[0027] like Then the damage state of the open circuit component has no obvious change;
[0028] like The damage state of the open circuit component changes significantly;
[0029] like Then the damage state of the open circuit component changes, but the change is not obvious;
[0030] in, is the damage-hysteresis loop correlation coefficient of the open-circuit component, obtained by experiment.
[0031] On the basis of the above technical solution, preferably, the process of judging the damage state of the closed-circuit component is as follows:
[0032] make
[0033] If A<Δ1 or B<Δ2, the damage state of the closed-circuit component does not change significantly;
[0034] like and at this time The damage state of the closed-circuit components changes significantly;
[0035] If A>Δ1, B>Δ2 and at this time Then the damage state of the closed-circuit components changes, but the change is not obvious;
[0036] in, is the damage-hysteresis loop correlation coefficient of the closed-circuit component, is the damage-basic magnetization curve correlation coefficient of the closed-circuit component, all obtained from experiments.
[0037] On the basis of the above technical solution, preferably, the magnetic property measurement process of the open circuit component includes:
[0038] Selecting measurement conditions, measuring the hysteresis loop of the open-circuit component under the measurement conditions, wherein excitation is applied during the measurement to make the open-circuit component reach magnetic saturation;
[0039] Calculate the horizontal coordinate of the intersection of the hysteresis loop of the open-circuit component and the X-axis in the first quadrant, and use the horizontal coordinate as the coercive force data of the open-circuit component;
[0040] Under the test conditions, the hysteresis loop of the open-circuit component is measured n times to obtain n coercive force data, and the n coercive force data are averaged to obtain the average coercive force data of the open-circuit component.
[0041] On the basis of the above technical solution, preferably, the magnetic property measurement process of the closed-circuit component includes:
[0042] Selecting test conditions, and testing the hysteresis loop and basic magnetization curve of the closed-circuit component using a closed-loop test device under the test conditions, wherein the closed-loop test device is provided with one or more excitation coils and induction coils;
[0043] Calculate the abscissa of the intersection of the hysteresis loop of the closed-circuit component with the X-axis in the first quadrant, and use the abscissa as the coercive force data of the closed-circuit component;
[0044] Before testing the basic magnetization curve, the closed-circuit component is demagnetized until it reaches the zero point, and then the basic magnetization curve is tested, and the initial value of the basic magnetization curve is used as the initial magnetic permeability data of the closed-circuit component;
[0045] Under the test conditions, the hysteresis loop and basic magnetization curve of the closed-circuit component are measured n times to obtain n coercive force data and n initial magnetic permeability data. The n coercive force data are averaged to obtain the average coercive force data of the closed-circuit component, and the n initial magnetic permeability data are averaged to obtain the average initial magnetic permeability data of the closed-circuit component.
[0046] The method of the present invention has the following beneficial effects compared with the prior art:
[0047] (1) The present invention can quickly and effectively determine the internal stress changes of metal components in high-end equipment, and the testing process is easy to implement. Various damage models and non-destructive evaluations can be further performed on the materials, thereby effectively guiding scientific experiments and industrial production.
[0048] (2) On the one hand, the present invention uses equipment to test the hysteresis loop or basic magnetization curve of metal components to obtain data such as coercive force and magnetic permeability; on the other hand, the change in its damage state is judged by the degree of change in coercive force and magnetic permeability, thereby realizing non-destructive testing of the magnetic properties of metal components of high-end equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0050] Figure 1 The figure is a flow chart of a method according to an embodiment of the present invention. DETAILED DESCRIPTION
[0051] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0052] like Figure 1 As shown, the present invention provides a method for nondestructive testing of magnetic properties of metal components, comprising the following steps:
[0053] S1: Clean impurities on the surface of metal components;
[0054] S2: Predict the magnetic properties of the metal component n times according to the shape of the metal component, and obtain the magnetic property test error based on the average magnetic property data of the metal component predicted n times;
[0055] S3: Perform n formal measurements on the magnetic properties of the metal component, calculate a damage evaluation index based on the average magnetic property data of the metal component obtained from the n formal measurements, and determine the damage state of the metal component based on the damage evaluation index and the magnetic property test error.
[0056] Specifically, in step S1, impurities on the surface of the metal material are divided into magnetic and non-magnetic impurities, and their presence will affect the real magnetic parameters of the test material, mainly by affecting its magnetization and demagnetization process and thus affecting the coercive force and magnetic permeability. Therefore, polishing, cleaning and other means are used to remove surface impurities.
[0057] Considering the domain wall displacement during the magnetization reversal process, the coercive force and initial permeability determined by the impurity theory are:
[0058]
[0059] Where: β is the doping concentration; μ0 is the vacuum permeability; μ i is the initial magnetic permeability; Ms is the saturation magnetic induction intensity; K1 is the magnetocrystalline anisotropy constant.
[0060] Specifically, in the present invention, the shape of the metal component is an open circuit component or a closed circuit component. The magnetic properties of the metal component include coercive force and initial magnetic permeability, and the magnetic property test error includes a coercive force test error Δ1 and an initial magnetic permeability test error Δ2.
[0061] Specifically, according to the different shapes of metal components, corresponding tooling conditions are selected to carry out magnetic performance testing. For open-circuit components, the magnetic performance measurement process includes:
[0062] A measurement condition is selected, under which a hysteresis loop of the open-circuit component is measured, wherein excitation is applied during the measurement to cause the open-circuit component to reach magnetic saturation.
[0063] Specifically, for components with open circuits, the hysteresis loop is tested by means of a vibrating sample magnetometer or an electromagnet scanning method, wherein the excitation field needs to make the workpiece reach magnetic saturation (the magnitude of the magnetic field is determined by the size of the workpiece and the test conditions). Specifically, for small-sized workpieces (V = 1-3mm 3 ) or sampleable test workpieces can be tested using a vibrating sample magnetometer, and workpieces with flat end faces can be tested using an electromagnet scanning method.
[0064] Calculate the horizontal coordinate of the intersection of the hysteresis loop of the open-circuit component and the X-axis in the first quadrant, and use the horizontal coordinate as the coercive force data of the open-circuit component;
[0065] Under the test conditions, the hysteresis loop of the open-circuit component is measured n times to obtain n coercive force data, and the n coercive force data are averaged to obtain the average coercive force data of the open-circuit component.
[0066] For closed-circuit components, the magnetic properties measurement process includes:
[0067] A test condition is selected, and a closed-loop test device is used to test a hysteresis loop and a basic magnetization curve of the closed-circuit component under the test condition, wherein the closed-loop test device is provided with one or more excitation coils and induction coils.
[0068] Specifically, for annular closed-circuit components, the winding method is used to test its hysteresis loop and basic magnetization curve. Testing the hysteresis loop requires excitation to saturate the workpiece, while the basic magnetization curve only requires a small external magnetic field. Specifically, in order to ensure uniform distribution of magnetic field intensity inside the sample, the outer and inner diameter ratio of the ring is required to be less than 1.1. Before the test, the ring is measured, weighed, wrapped with insulating tape, and first wound with the induction coil N2, then the excitation coil N1, and the coil ends are depainted.
[0069] In this embodiment, a closed circuit component is placed in a closed magnetic circuit, including one or more excitation coils and induction coils. The excitation coil is used to generate a magnetic field, and the induction coil is used to measure the magnetic flux passing through the component. A fluxmeter is used to measure the magnetic flux passing through the component, thereby calculating the magnetic field and magnetic permeability.
[0070] In the test, a gradually increasing magnetic field is applied to the excitation coil until it reaches saturation, then gradually decreases to zero, then increases in the opposite direction to saturation, and finally returns to zero. This process forms a complete hysteresis loop.
[0071] Specifically, by controlling the constant current power supply to provide current I to the excitation coil, if the circumference of the magnetic circuit of the magnetic ring is Le, the magnetic field intensity generated is:
[0072] H = N1*I / Le (3);
[0073] The induced voltage U of the induction coil is integrated to obtain the magnetic flux φ. If the cross-sectional area of the sample is S, the magnetic flux density can be calculated:
[0074] B = φ / (N2*S) (4);
[0075] Among them: the number of turns of N2 is determined by the range and resolution of the fluxmeter, and the number of turns of N1 is determined by the minimum magnetic field of the workpiece magnetic saturation and the current output of the current source.
[0076] Then output the BH curve to obtain the magnetic permeability data.
[0077] The coercive force is the point in the hysteresis loop where the magnetic flux density is still not zero when the magnetic field intensity is zero. Calculate the horizontal coordinate of the intersection of the hysteresis loop of the closed circuit component with the X-axis in the first quadrant and use the horizontal coordinate as the coercive force data of the closed circuit component.
[0078] Before testing the basic magnetization curve, the closed-circuit component is demagnetized until it reaches the zero point, and then the basic magnetization curve is tested, and the initial value of the basic magnetization curve is used as the initial magnetic permeability data of the closed-circuit component;
[0079] Under the test conditions, the hysteresis loop and basic magnetization curve of the closed-circuit component are measured n times to obtain n coercive force data and n initial magnetic permeability data. The n coercive force data are averaged to obtain the average coercive force data of the closed-circuit component, and the n initial magnetic permeability data are averaged to obtain the average initial magnetic permeability data of the closed-circuit component.
[0080] In the present invention, the process of n times of pre-measurement and n times of formal measurement is as described above. First, for metal components of different shapes, n times of pre-measurement are performed, and n should be greater than or equal to 5, so as to obtain the test error range Δ (percentage) of the metal components under the test conditions, which can avoid the randomness of the test data and improve the accuracy. After that, the metal components are formally measured, and the measurement method is still the same as the pre-measurement. At this time, n times of formal measurement are also required, and the damage evaluation index of the metal components is calculated according to the measured average magnetic property data, and the damage state of the metal components is judged according to the damage evaluation index and the magnetic property test error obtained in the pre-measurement.
[0081] Specifically, for an open-circuit component, the magnetic property measured is coercive force, and the average magnetic property data is the average coercive force data. After n pre-measurements and n formal measurements, the average coercive force data is calculated in the same manner, and the expression can be shown as follows:
[0082]
[0083] In the formula, Hc e Represents the average coercivity data obtained from n measurements, Hc max and Hc min are the maximum and minimum values of the coercivity data obtained from n measurements, where n is the number of measurements.
[0084] For closed-circuit components, when measuring their magnetic properties, it is necessary to measure the coercive force data and the initial magnetic permeability data. After n pre-measurements and n formal measurements, the method of calculating the average coercive force data and the average initial magnetic permeability data is the same, and the formula for calculating the average coercive force data of closed-circuit components is the same as that of open-circuit components, which will not be repeated here. The calculation formula for the average initial magnetic permeability data is as follows:
[0085]
[0086] In the formula, represents the average initial permeability data obtained from n measurements, and are the maximum and minimum values of the initial magnetic permeability data obtained from n measurements, where n is the number of measurements.
[0087] In this embodiment, for the open-circuit component, the magnetic performance test error is Δo, and Δo=Δ1; for the closed-circuit component, the magnetic performance test error is Δc, and Δc=Δ1+Δ2.
[0088] Regardless of whether it is an open circuit component or a closed circuit component, the formula for calculating Δ1 is the same. The specific calculation formula for the coercive force test error Δ1 is:
[0089]
[0090] Where Hc represents the coercivity data, Hc max and Hc min Hc is the maximum and minimum coercivity data obtained in n times of prediction. e is the average coercivity data obtained in n times of prediction;
[0091] For closed-circuit components, the calculation formula for the initial magnetic permeability test error Δ2 is:
[0092]
[0093] In the formula, μ i represents the starting magnetic permeability data, and are the maximum and minimum initial permeability data obtained in n times of prediction, is the average initial magnetic permeability data obtained in n pre-measurements.
[0094] Specifically, the present invention first performs n times of pre-measurement on the open circuit component or closed circuit component according to the above-mentioned method and formula, and calculates the average coercive force data and the average initial magnetic permeability data according to the above-mentioned formula (5) or formula (6) based on the results of the n times of pre-measurement, and calculates Δ1 and Δ2 according to the average coercive force data and the average initial magnetic permeability data according to formula (7) and formula (8), and then calculates the magnetic property test error Δo or Δc of the open circuit component or closed circuit component according to Δ1 and Δ2, and then performs n times of formal measurement on the open circuit component or closed circuit component, and calculates the average coercive force data and the average initial magnetic permeability data according to the above-mentioned formula (5) or formula (6) based on the results of the n times of formal measurement, and calculates the damage evaluation index according to the formally measured average coercive force data and the average initial magnetic permeability data. Finally, the damage state is judged based on the damage evaluation index and the magnetic property test error.
[0095] The coercivity and initial permeability determined by stress theory are:
[0096]
[0097] Where: σ is the internal stress; λ sis the saturation magnetostriction coefficient; μ0 is the vacuum magnetic permeability; Ms is the saturation magnetic induction intensity; μ i is the starting magnetic permeability.
[0098] Specifically, for open circuit components, the damage evaluation index is for:
[0099]
[0100] In the formula, is the correlation constant of the open circuit component, with a value of 0.85-1.25, which is related to the physical properties of the component material; It is the average coercive force change rate data obtained from n formal measurements of the open circuit component.
[0101] The judgment process of the damage state of the open circuit component is:
[0102] like Then the damage state of the open circuit component has no obvious change;
[0103] like The damage state of the open circuit component changes significantly;
[0104] like Then the damage state of the open circuit component changes, but the change is not obvious;
[0105] in, is the damage-hysteresis loop correlation coefficient of the open-circuit component, obtained by experiment.
[0106] Specifically, for closed-circuit components, the damage assessment index is for:
[0107]
[0108] In the formula, is the correlation constant of the closed-circuit component, with a value of 0.85-1.25, which is related to the physical properties of the component material; is the structural coefficient of the closed-circuit component, which is 1-1.05 and is related to the ratio of the outer diameter to the inner diameter of the ring; is the average coercive force change rate data of the closed-circuit component obtained in n formal measurements; It is the average initial permeability change rate data of the closed-circuit component obtained in n formal measurements.
[0109] The process of judging the damage status of closed-circuit components is as follows:
[0110] make
[0111] If A<Δ1 or B<Δ2, the damage state of the closed-circuit component does not change significantly;
[0112] like and at this time The damage state of the closed-circuit components changes significantly;
[0113] If A>Δ1, B>Δ2 and at this time Then the damage state of the closed-circuit components changes, but the change is not obvious;
[0114] in, is the damage-hysteresis loop correlation coefficient of the closed-circuit component, is the damage-basic magnetization curve correlation coefficient of the closed-circuit component, all obtained from experiments.
[0115] Furthermore, the correlation between various types of damage (such as dislocation, grain boundary, hole crack, stress, etc.) and the changes in magnetic parameters can be established.
[0116] It should be noted that if the magnetic parameter change of the metal component is not as described above, it indicates that there is a problem in the test process and the test needs to be repeated. In this case, it is necessary to start from step S1 again and perform nondestructive testing again according to the method of the present invention.
[0117] The method of the present invention is further described below in conjunction with two specific embodiments:
[0118] Example 1
[0119] In this embodiment, the bearing material of Hangfa M50 material (after 20% cold rolling deformation and quenching and tempering treatment) is taken as an example, and its cross section is 10×6mm 2 , with a height of 18mm. Since it is an open-circuit component, the coercive force is used to detect its damage. The hysteresis loop before and after the electromagnetic impact process is tested many times to obtain the coercive force before and after the treatment. A non-destructive detection method for the magnetic properties of metal components is implemented in the following steps:
[0120] (1) Clean the surface impurities of the test sample
[0121] The workpiece is ground and cleaned of surface impurities, and #80 sandpaper is used to remove the surface oxide layer and doping.
[0122] (2) Magnetic property test of the workpiece
[0123] According to the shape and size characteristics of the material, the hysteresis loop of the workpiece is tested multiple times with a vibrating sample magnetometer before and after the electromagnetic impact on the workpiece. The curve is processed to obtain the horizontal coordinate of the intersection with the X-axis in the first quadrant, that is, the coercive force data.
[0124] Table 1 Coercivity prediction
[0125] Prediction 1 2 3 4 5 Coercivity(Oe) 33.9 34.2 33.4 33.6 32.8
[0126] Calculated
[0127] Hc max =34.2(Oe),Hc min =32.8(Oe)
[0128]
[0129] Table 2 Coercivity test before and after electromagnetic shock
[0130]
[0131]
[0132] The average coercive force before electromagnetic shock is calculated as:
[0133]
[0134] The average coercive force after electromagnetic shock is:
[0135]
[0136] Calculations show that the coercivity decreased by 15.8% after treatment.
[0137] (3) Evaluation of damage status changes
[0138] The coercivity data of the workpiece under the same state were tested many times, indicating that the test method Δo = Δ1 = 2.3%, which is considered to be within the range of 2.3% for the workpiece under this material state. The above changes are effective changes, that is, the coercivity change exceeds 2.3%, which is considered to be a change in its microstructure. Combined with the analysis of dislocation density under different coercivity by X-ray diffractometer, it can be known that the state of the material is 10% to 15%, and the material damage evaluation index is It is believed that the workpiece has been effectively treated, the damage state has changed significantly, and its internal stress has been regulated and significantly reduced under electromagnetic shock.
[0139] The technical effect comparison of the coercivity reduction degree of the above embodiment and the actual residual stress test results of the batch of samples shows that the residual stress in the electromagnetic impact direction before and after the electromagnetic impact is reduced from -271MPa to -193.4MPa, a decrease of 28.1%. The residual stress perpendicular to the electromagnetic impact direction is reduced from -338.1MPa to -149.8MPa, a decrease of 55.5%.
[0140] Example 2
[0141] In this embodiment, a bearing ring component made of AERON M50 material is taken as an example, with an outer diameter of 90 mm, an inner diameter of 85 mm, and a height of 20 mm. Since it is a closed-circuit component, coercive force and magnetic permeability are used to perform damage detection on it, and its hysteresis loop and basic magnetization curve before and after electromagnetic impact treatment are tested multiple times. A non-destructive detection method for magnetic properties of metal components is implemented in the following steps:
[0142] (1) Clean the surface impurities of the test sample
[0143] The workpiece is ground and cleaned of surface impurities, and #80 sandpaper is used to remove the surface oxide layer and doping.
[0144] (2) Magnetic property test of the workpiece
[0145] According to the shape and size characteristics of the material, the winding impact method was used to test the hysteresis loop and basic magnetization curve of the workpiece multiple times before and after the electromagnetic impact. The calculation results show that N1=250, N2=30, the initial magnetization field is 80A / m, and the maximum magnetization field is set to 5500A / m. The curve is processed to obtain the ratio of B to H at the initial magnetization point, that is, the initial magnetic permeability data.
[0146] Table 3 Prediction of initial magnetic permeability
[0147] Prediction 1 2 3 4 5 Magnetic Permeability 88.3 90.5 87.2 87.7 92.6
[0148] Calculated
[0149]
[0150]
[0151] Table 4 Initial magnetic permeability test before and after electromagnetic shock
[0152] Before electromagnetic shock 88.3 90.5 87.2 87.7 92.6 After electromagnetic shock 97.8 99.2 99.6 97.4 98.2
[0153] The average initial magnetic permeability before electromagnetic shock is calculated as follows:
[0154]
[0155] The average initial magnetic permeability after electromagnetic shock is:
[0156]
[0157] Calculations show that the initial magnetic permeability increased by 10.8% after treatment.
[0158] Table 5 Coercivity correction error test
[0159] Error test 1 2 3 4 5 Coercivity(Oe) 25.6 26.1 26.3 26.6 25.5
[0160] Calculated
[0161] Hc max= 26.6(Oe),Hc min= 25.5(Oe)
[0162]
[0163] Table 6 Coercivity test before and after electromagnetic shock
[0164] Coercivity before electromagnetic shock (Oe) 25.6 26.1 26.3 26.6 25.5 Coercivity after electromagnetic shock (Oe) 23.5 22.8 23.1 21.9 23.6
[0165] The average coercive force before electromagnetic shock is calculated as:
[0166]
[0167] The average coercive force after electromagnetic shock is:
[0168]
[0169] Calculations show that the coercivity decreased by 11.2% after treatment.
[0170] (3) Evaluation of damage status changes
[0171] The initial permeability and coercivity data of the workpiece in the same state were tested many times, indicating that the test error of this method is Δc=Δ1+Δ2=2.3%+3.6%=5.9%. For the workpiece in the initial state, it is considered that the changes of the two magnetic parameters that are simultaneously greater than their critical change rates are effective changes. Combined with the analysis of dislocation density under different initial permeabilities by X-ray diffractometer, it can be known that the state of the material is 5% to 10%, 5% to 10%.
[0172] at this time Therefore, it was found through calculation that the workpiece was effectively treated after the electromagnetic shock, and its internal stress was regulated and significantly reduced under the electromagnetic shock.
[0173] The degree of change in the magnetic properties of the above embodiment was compared with the actual residual stress test results of the batch of bearing rings. It was found that the residual stress of the raceway before and after the electromagnetic impact was -140.9MPa and -86.4MPa, respectively, with a decrease of 38.7%.
[0174] This shows that the method of the present invention can quickly and effectively determine the internal stress changes of metal components in high-end equipment, and the testing process is easy to implement. Various damage models and non-destructive evaluations of materials can be further established, thereby effectively guiding scientific experiments and industrial production.
[0175] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for nondestructive testing of magnetic properties of metal components, characterized in that: The steps include: S1: Clean impurities on the surface of metal components; S2: Predict the magnetic properties of the metal component n times according to the shape of the metal component, and obtain the magnetic property test error based on the average magnetic property data of the metal component predicted n times; S3: Perform n formal measurements on the magnetic properties of the metal component, calculate a damage evaluation index based on average magnetic property data of the metal component obtained from the n formal measurements, and determine the damage state of the metal component based on the damage evaluation index and the magnetic property test error; The shape of the metal component is an open circuit component or a closed circuit component; The magnetic properties of metal components include coercivity and initial magnetic permeability. The magnetic properties test error includes the coercivity test error. 1 and initial permeability test error 2; When the shape of the metal component is an open circuit component, the measured magnetic property is coercive force, the average magnetic property data is the average coercive force data, and the magnetic property test error is o, and o= 1; When the shape of the metal component is a closed-circuit component, the measured magnetic properties are coercive force and initial magnetic permeability, and the average magnetic property data are average coercive force data and average initial magnetic permeability data. The magnetic property test error is c, and c= 1+ 2; Damage evaluation index of open circuit components for: ; In the formula, is the related constant of the open circuit component, and its value is 0.85-1.25; is the average coercive force change rate data obtained from n formal measurements of the open circuit component; The judgment process of the damage state of the open circuit component is: like , then the damage state of the open circuit component has no obvious change; like , then the damage state of the open circuit component changes significantly; like , then the damage state of the open circuit component changes, and the change is not obvious; in, is the damage-hysteresis loop correlation coefficient of the open-circuit component, obtained by experiment.
2. A nondestructive testing method for magnetic properties of metal components as claimed in claim 1, characterized in that: Coercivity test error The calculation formula for 1 is: ; Where Hc represents the coercive force data, and are the maximum and minimum coercive force data obtained in n times of prediction, is the average coercivity data obtained in n times of prediction; Initial permeability test error The calculation formula for 2 is: ; In the formula, represents the starting magnetic permeability data, and are the maximum and minimum initial permeability data obtained in n times of prediction, is the average initial magnetic permeability data obtained in n pre-measurements.
3. A nondestructive testing method for magnetic properties of metal components as claimed in claim 1, characterized in that: Damage evaluation index of closed circuit components for: ; In the formula, is the related constant of the closed circuit component, and its value is 0.85-1.25; is the structural coefficient of the closed-circuit component, and its value is 1-1.05; is the average coercive force change rate data of the closed-circuit component obtained in n formal measurements; is the average initial permeability change rate data of the closed-circuit component obtained in n formal measurements; The process of judging the damage status of closed-circuit components is as follows: make , ; like or , then the damage state of the closed-circuit components has no obvious change; like and ,at this time , then the damage state of the closed-circuit components changes significantly; like , And at this time , then the damage state of the closed-circuit components changes, and the change is not obvious; in, is the damage-hysteresis loop correlation coefficient of the closed-circuit component, is the damage-basic magnetization curve correlation coefficient of the closed-circuit component, all obtained from experiments.
4. A nondestructive testing method for magnetic properties of metal components as claimed in claim 1, characterized in that: The process of measuring the magnetic properties of open circuit components includes: Selecting measurement conditions, measuring the hysteresis loop of the open-circuit component under the measurement conditions, wherein excitation is applied during the measurement to make the open-circuit component reach magnetic saturation; Calculate the horizontal coordinate of the intersection of the hysteresis loop of the open-circuit component and the X-axis in the first quadrant, and use the horizontal coordinate as the coercive force data of the open-circuit component; Under the test conditions, the hysteresis loop of the open-circuit component is measured n times to obtain n coercive force data, and the n coercive force data are averaged to obtain the average coercive force data of the open-circuit component.
5. A nondestructive testing method for magnetic properties of metal components as claimed in claim 1, characterized in that: The magnetic properties measurement process of closed-circuit components includes: Selecting test conditions, and testing the hysteresis loop and basic magnetization curve of the closed-circuit component using a closed-loop test device under the test conditions, wherein the closed-loop test device is provided with one or more excitation coils and induction coils; Calculate the abscissa of the intersection of the hysteresis loop of the closed-circuit component with the X-axis in the first quadrant, and use the abscissa as the coercive force data of the closed-circuit component; Before testing the basic magnetization curve, the closed-circuit component is demagnetized until it reaches the zero point, and then the basic magnetization curve is tested, and the initial value of the basic magnetization curve is used as the initial magnetic permeability data of the closed-circuit component; Under the test conditions, the hysteresis loop and basic magnetization curve of the closed-circuit component are measured n times to obtain n coercive force data and n initial magnetic permeability data. The n coercive force data are averaged to obtain the average coercive force data of the closed-circuit component, and the n initial magnetic permeability data are averaged to obtain the average initial magnetic permeability data of the closed-circuit component.
Citation Information
Patent Citations
Method for measuring parameter of magnetic characteristic of permanent magnet
CN101561480A
Method for detecting coercive force of armature parts
CN114487950A